PERBANDINGAN PENGATURAN BANK TANAH DI NEGARA INDONESIA DAN BELANDA - Roma Tua Situngkir; Sri Untari Indah Artati (Reformasi Hukum Trisakti, 2022)
According to Government Regulation Number 64 of 2021, which is based on article 1 paragraph (1), the Land Bank is a special institution (sui generis) established by the central government and is given specific authority to control land. The Land Bank, according to the Dutch government agency Dienst Landdelijk Gebied (DLG), is the systematic acquisition and short-term management of rural land by a disinterested state agency with the intention of redistributing and/or leasing this land in order to improve agricultural structures and/or allocating return of land for other purposes in the public interest. The question is: How do the land bank arrangements in Indonesia and the Netherlands compare and contrast, and what are the underlying causes of these similarities and differences in land bank arrangements in Indonesia and the Netherlands? This type of research is normative, descriptive research, uses inferior information, qualitative analysis, and the conclusions use deductive logic. The conclusions in this research, 1) The similarities and differences of Land Banks in Indonesia and the Netherlands as well as the factors of the similarities, namely the legal system and the needs and factors of differences, namely the concepts adopted by the countries of Indonesia and the Netherlands.